Quality care for quality life : the model nursing home: a strategic public communications campaign to increase awareness for Man Fut Tong nursing home. - Ng, Yun Shiean. (2008)
This Final Year Project consist of 2 parts. Part 1: Report and Appendix A-N & Part 2: Appendix O-S. This report represents a year-long campaign to raise awareness of Man Fut Tong Nursing Home (MFTNH) conducted by us under the agency name: cLove communications. Following systems theory (Simmons, 1990), we conducted formative research to aid in the campaign planning and execution. It showed that most Singaporeans do not know of the Home (83.5%) and most of the existing volunteers do not initiate ways to help our client.